Measuring Structural Unemployment: Is There a Rough and Ready Answer? - Steinar Holden; Ragnar Nymoen (Norges Bank, 1998)
In recent years, the OECD has measured the structural rate of unemployment by an indicator called the Non-Accelerating Wage Rate of Unemployment. The NAWRU indicator is an important element in the policy analysis of the OECD. The rise in the estimated NAWRUs is also taken as evidence that Nordic unemployment, as well as unemployment in the rest of Europe, has increased due to a malfunctioning of labour markets. The paper presents stable empirical wage equations for Denmark, Finland, Norway and Sweden over the period 1964-1994, in sharp contrast to the increased NAWRU estimates. The instability of the NAWRU estimates is the product of a misspecified underlying wage equation, and not due to instability in the wage setting itself.
hdl:11250/2500572
Keywords: 330; NAWRU indicator; structural unemployment; econometric wage equations; stability; nordic wage formation